Interdisciplinary and practical approaches to managerial education and training - Pardal, Pedro; Teixeira, Nuno Miguel; Carvalho, Luísa Cagica (IGI Global, 2022)
"This book addresses the main topics of interest regarding the best practices, laboratory methods, policies, protocols, in the areas of business education and managerial training offering topics related to practical approaches to managerial education and training
Includes bibliographical references and index
Chapter 1. Insights into preparing training courses on financial services for entrepreneurs in Africa -- Chapter 2. Distance education in higher education: modern applications and management courses -- Chapter 3. Blended learning compared to online learning in business, management, and accounting education: a bibliometric analysis and literature review -- Chapter 4. Key factors for entrepreneurial success: a synthesis of earlier research and an agenda proposal to support entrepreneurial training -- Chapter 5. Corporate simulation and the articulation of the problem-based learning methodology with the continuous assessment model -- Chapter 6. Transforming tourism education: an interdisciplinary approach to sustainable tourism management -- Chapter 7. Evaluation of the potential of ideation tools to create technologies aimed at education -- Chapter 8. Employee engagement and learning for the transformational leader -- Chapter 9. Online learning or emergency remote teaching?: reflections on online learning as pedagogical innovation in a higher education institution -- Chapter 10. Preparing managers to lead for diversity, equity, and inclusion -- Chapter 11. The importance of social components in online learning: the case of business administration online at MCI -- Chapter 12. Adult learning in the workplace: critical application and new mediums -- Chapter 13. Creativity processes applied to the innovation management of a digital showroom for cars -- Chapter 14. The role of evaluation in service learning in economics and business: systematic review and proposal of evaluation -- Chapter 15. Socio-intercultural management competencies -- Chapter 16. Leader effects on engagement. - Mode of access: World Wide Web
Keywords: Management -- Study and teaching; Business education; Executives -- Training of